Text rhythmic system: Its energetic and subliminal potentials - Alla Kalyta (LingBaW)
The article introduces scientific considerations concerning the energetic nature and origin of rhythm subliminal potential in a spoken text as well as the mechanisms of its impact on the recipient. The paper advances the idea that rhythm energetics and its subliminal potential is based on such postulates: (1) rhythm is generated in the speaker’s psyche at the levels of his/her unconscious (or existential being) and subconscious (or mental and transcendental beings) spheres; (2) the text rhythmic system has a definite emotional and pragmatic potentials that realize a latent manipulative and subliminal influence; (3) generation of the spoken text tempo-rhythm is carried out by means of integrating micro-rhythms of all levels of the speaker’s inner speech into the internal macro-rhythm, which is materialized in the form of an outer tempo-rhythm as a complex means of achieving a subliminal effect of speech. The article also outlines the prospects of studying a subliminal nature of rhythm.